Activated carbon produced from pigeon peas hulls waste as a low-cost agro-waste adsorbent for Cu(II) and Cd(II) removal. Issue 15 (27th March 2016) - Venkata Ramana, D.K.; Min, Kim
Abstract: Pigeon peas hulls (PPH) as an agro-waste by-product and activated carbon produced from PPH (APPH) were used as effective and efficient adsorbents for the removal of Cu(II) and Cd(II) from aqueous solutions. The adsorbents were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction and Brunauer, Emmett and Teller surface area measurements. The influence of various parameters, such as the effect of pH, adsorbent dose, contact time, initial metal ion concentration, and temperature, were evaluated. The experiments showed that the removal of metal ions followed a pseudo-second-order kinetic model and equilibrium adsorption studies confirmed that the Langmuir model provided a better-fit, and showed that APPH has greater potential than PPH. The thermodynamic properties, i.e. (Δ G °), (Δ H °), and (Δ S °), showed that the adsorption of Cu(II) and Cd(II) onto PPH and APPH was endothermic, spontaneous, and feasible over the temperature range, 293–313 K.